Citizenship : identity, institutions and the postmodern challenge - Kalu, Kalu Ndukwe (Routledge, Taylor & Francis Group, 2017)
In stark contrast to previous scholarship about citizenship as a construct, this groundbreaking book covers the full spectrum of literature on citizenship theory, including the state and structure of identity, the individual and the public, and the enduring issues of civic engagement and collective discourse. It examines some of the complex challenges faced by citizens and policy makers and explores the existing procedural and institutional mechanisms that undermine democratic political accountability as well as its legitimation. Drawing from classical conceptions of citizenship in the early Greco-Roman eras to the more contemporary critical social theory and postmodernist contentions, the work casts a wide net that covers complex issues including rights and obligation, the doctrine of state sovereignty and authority, equality, the principle of majority rule, citizen participation in governance, public versus self-interest, ideas of justice, immigration and cultural identity, global citizenship, and the evolution of hybrid communities that challenge traditional notions of state-citizenship identity. With meticulous detail and powerful analysis, author Kalu N. Kalu unceasingly places citizenship as the central thesis of this project, illuminating its intellectual richness on the one hand, and demonstrating the ongoing challenges in both conceptualization and practice, on the other.